Onder-Kouga: Oorsig van 'n kontrei - O.J.O. Ferreira (Contree)
Lower-Kouga, situated north of the Langkloof Valley, was mentioned by early travellers, but was probably never visited by them. The earliest indication of Whites living in the region is found in a reference by Thunberg written in 1773. By 1815 all the most important farms in the Lower-Kouga were already occupied. The population lives in scattered communities and the region is still the heartland of the Gerbers and Ferreiras. The harshness of the region resulted in the inhabitants' developing a specific character, while topographical factors influenced the outlay of farms and the construction of homes. Citrus production was originally the main source of income, but in course of time has been replaced, in importance, by stock-farming and deciduous fruits. The seclusion of the region was only ended during the late 1930s, but owing to the work of clergy, local members of the church council, and teachers at farm schools, mental and moral decay did not set in. The seclusion did, however, influence recreational activities and eating habits, and aided the development of home remedies. The gradual depopulation of the Lower-Kouga is an ongoing process, but with its beautiful scenery the region has tourist potential.